STUDY OF RUNOFF IN UNDA WATERSHED - SATRIA WAHYU 0ETOM0; Takahiro Osawa; I Nyoman Merit (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science), 2011)
When rain falls on the earth, it just does not sit there, it starts moving according to the laws of gravity. A portion of the precipitation seeps into the ground to replenish Earth's groundwater. Most of it flows downhill as runoff. Runoff is extremely important in that not only does it keep rivers and lakes full of water, but it also changes the landscape by the action of erosion. The purpose and objective in this study are to estimate the conditions of land cover of Unda Watershed based on the results of image processing, to estimate the monthly average runoff and discharge in outlet of Unda Watershed from 1999 to 2003. The research location is in Unda Watershed. This watershed lies in Province of Bali which has wide 233.1 km2 (23.310 Ha) (Balai Wilayah Sungai Bali-Penida). Administratively this watershed lies in 3 Regencies that are Karangasem, Klungkung and Bangli Regency. Mostly the region lies in the Karangasem Regency. In this research, the monthly rainfall data employed to generate the runoff process. Analyze of contour map from topography map obtained the watershed area, physical parameter of river and concentration time. In this research used monthly average rainf all data (from 1999 to 2003) from Pempatan, Besakih, Singarata, Sidemen, Klungkung, Telengan, Rain Gauge Station and Polygon Thiesen method employed to analyze the datas. Apart of rainfall, there are a number of site specific factors which have a direct bearing on the occurrence and volume of runoff, they are soil type, land cover and slope. The soil types in this research area are all Regosol, this soil mapping does not need to be overlayed in obtaining the land unit. Analyze of land cover was employed by Supervised Classification method. By image processing obtained land cover of Unda Watershed estimated consists of 38.129 km2 of forest area (16.357°Ai), 19.122 km2 of grassland area (8.203%), 100.991 km2 of farmland area (43.325%), 62-412 km2 of area housing (26.775%), 2.625 km2 of water area (1.126%), 4.046 km2 of cloud area (1.736%), 2.327 km2 cloud shadows (0.998%) and 3-448 km2 of stone area (1.749%). The results of runoff by Nakayasu Unit Hydrograph and Melchior Method gives quite similar patterns. The Melchior method gives higher runoff values. This method estimates total runoff while Nakayasu Unit Hydrograph estimates runoff by dividing rainfall into hours. By Nakayasu Unit Hydrograph Method showed the average of monthly average runoff were 10.61 m3/s and 18.67 m3/s by Melchior Method. The different percentage between these methods was 59.71%. By summing runoff and the baseflow obtained river discharge and the average of river discharge in this thesis was 22.63 m3/s. Observed river discharge from Water Level Recorder (WLR) Unda Dam was used in validation, the average of monthly average river discharge was 18.24 m3/s. The different percentage between these methods was 66.37%.